The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/10643389.2020.1806685
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and efficacy of disinfection in ceramic water filters: A critical review

Abstract: Diarrheal illnesses claim the lives of hundreds of thousands of children each year, most of whom live in rural and low-income communities. Ceramic Water Filters (CWF) are widely regarded as one water treatment technology with the potential to increase access to safe drinking water. While physical filtration mechanisms are a key contributor to improving the water safety, silver is commonly added to improve disinfection performance. Therefore, a thorough review of silver disinfection efficacy and disinfection me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 106 publications
(228 reference statements)
0
46
0
Order By: Relevance
“…Comparatively, when zinc is in isolation, these effects thus weaken the cells, but the rate of cell degradation may not be as high as when facilitated with the presence of other metals, as was found in this research. When metal combinations were added, cells became more vulnerable to attack from the silver present within the mixture, which may have (1) caused cell lysis directly by bonding with the cell membrane and causing pits, (2) penetrated the cell membrane and bonded directly with DNA in the cytoplasm, leading to degradation, and/or (3) reacted to create ROS, as shown in Reaction (1), which degraded the cells through oxidative killing (Venis & Basu 2020). As such, the improved disinfection observed with Ag 67 ZnO 33 in comparison to the other metal mixtures thus likely resulted Figure 4 | LRVs achieved after 300 min of mixing under each of the synthetic water quality conditions evaluated and detailed in Table 1; pH values of 6.4 (low pH), 7.4 (mid pH), and 8.6 (high pH) with high (.8.4 mg/L) and low (,2.5 mg/L) DO.…”
Section: Comparison Of Combined Silver-zinc Disinfectionmentioning
confidence: 99%
“…Comparatively, when zinc is in isolation, these effects thus weaken the cells, but the rate of cell degradation may not be as high as when facilitated with the presence of other metals, as was found in this research. When metal combinations were added, cells became more vulnerable to attack from the silver present within the mixture, which may have (1) caused cell lysis directly by bonding with the cell membrane and causing pits, (2) penetrated the cell membrane and bonded directly with DNA in the cytoplasm, leading to degradation, and/or (3) reacted to create ROS, as shown in Reaction (1), which degraded the cells through oxidative killing (Venis & Basu 2020). As such, the improved disinfection observed with Ag 67 ZnO 33 in comparison to the other metal mixtures thus likely resulted Figure 4 | LRVs achieved after 300 min of mixing under each of the synthetic water quality conditions evaluated and detailed in Table 1; pH values of 6.4 (low pH), 7.4 (mid pH), and 8.6 (high pH) with high (.8.4 mg/L) and low (,2.5 mg/L) DO.…”
Section: Comparison Of Combined Silver-zinc Disinfectionmentioning
confidence: 99%
“…In CWFs, microorganisms interact with the small, tortuous pores in the matrix of the ceramic filters. 5,50,67 Therefore, the volume and surface area of a microorganism impacts the interactions, and subsequent retention, within the ceramic matrix. 57,58 Previous studies have shown that changing the diameter of microbial surrogates (analogous to virus-, 0.02 μm, through protozoan-sized, 10 μm) changed the log removal of a CWF from 1.5 to 3.2.…”
Section: Impact Of Water Chemistry On Cwf Performancementioning
confidence: 99%
“…Ceramic water filters (CWFs), a physical point-of-use (POU) drinking water treatment device, have been studied by many researchers. 1–5 CWFs are effective against a wide range of contaminants including bacteria, 6–10 organic and inorganic chemicals, 10 protozoa, 11 and viruses. 12–15 The reduction in pathogenic microorganisms has led to reductions in diarrheal rates ranging from 60–80% in Colombia, 7 South Africa, 6,16 Cambodia, 12,17–19 and other locations around the world.…”
Section: Introductionmentioning
confidence: 99%
“…CWFs are made of a mixture of clay and burn‐out materials (e.g. rice husks and sawdust) and often incorporate silver as nanoparticles (NPs) or nitrates 3 . CWFs are usually used in small groups or single families to treat water for drinking purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silver is expensive costing upwards of 1.66 USD g −1 for silver NPs (Argenol Laboratories, personal communication). Silver's relatively high cost significantly increases the total cost of a CWF, reducing its availability to target communities 3 . This raises the question as to the scope for using other metal NPs that may be obtained at a lower cost and that also display antimicrobial properties instead of, or in combination with, silver NPs.…”
Section: Introductionmentioning
confidence: 99%